2023
DOI: 10.3389/fpsyt.2023.1053502
|View full text |Cite
|
Sign up to set email alerts
|

The Patient and Carer Race Equality Framework: a model to reduce mental health inequity in England and Wales

Shubulade Mary Smith,
Amna Kheri,
Kevin Ariyo
et al.

Abstract: The Patient and Carer Race Equality Framework (PCREF) is an Organisational Competence Framework (OCF), recommended by the Independent Review of the Mental Health Act as a means to improve mental health access, experience and outcomes for people from ethnic minority backgrounds, particularly Black people. This is a practical framework that should be co-produced with and tailored to the needs of service users, based on quality improvement and place-based approaches. We aim to use the PCREF to address the longsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Clinicians in the current study explicitly highlighted a bias towards detaining Black men. This has been widely reported in other studies which have reported clinician biases and racial profiling being among the proposed explanations for the over-representation of Black men in detentions [10], and there are recent efforts to improve clinical practice and introduce unconscious bias training in mental health care [26]. Furthermore, this links with England and Wales government White Paper - Reforming the Mental Health Act [27].…”
Section: Discussionmentioning
confidence: 58%
“…Clinicians in the current study explicitly highlighted a bias towards detaining Black men. This has been widely reported in other studies which have reported clinician biases and racial profiling being among the proposed explanations for the over-representation of Black men in detentions [10], and there are recent efforts to improve clinical practice and introduce unconscious bias training in mental health care [26]. Furthermore, this links with England and Wales government White Paper - Reforming the Mental Health Act [27].…”
Section: Discussionmentioning
confidence: 58%
“…Addressing any inequalities of access to services and reducing racial discrimination and disparities appears to be a key issue to address across several mental health systems (21, 22, 74, 75). Service users from minoritised ethnic groups reported experiences of racism and unfair treatment, thus efforts to promote equality, diversity and inclusion and anti-racist practice are needed, a recent example of which is the Patient and Carer Race Equality Framework in England and Wales (76).…”
Section: Discussionmentioning
confidence: 99%
“…At a service system level, provision of community alternatives when in crisis [35] and focusing resources on long term, high quality and individualised community care in which service users are supported to participate in decisions and provided a broad range of help with supported self-management, medication management and social difficulties was supported by our findings as a potential means of reducing compulsory admission. A single participant referred to discrimination, but many participants felt disempowered and lacking a voice in the care, an experience to which racial inequalities may also have been relevant [36].…”
Section: Discussionmentioning
confidence: 99%